2016
DOI: 10.5194/acp-16-6335-2016
|View full text |Cite
|
Sign up to set email alerts
|

Will a perfect model agree with perfect observations? The impact of spatial sampling

Abstract: Abstract. The spatial resolution of global climate models with interactive aerosol and the observations used to evaluate them is very different. Current models use grid spacings of ∼ 200 km, while satellite observations of aerosol use so-called pixels of ∼ 10 km. Ground site or airborne observations relate to even smaller spatial scales. We study the errors incurred due to different resolutions by aggregating high-resolution simulations (10 km grid spacing) over either the large areas of global model grid boxe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
117
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(123 citation statements)
references
References 61 publications
2
117
0
Order By: Relevance
“…The arithmetic mean of observations is 17.4 ng g −1 , larger than the geometric mean of 12.7 ng g −1 and the median of 11.8 ng g −1 (see the vertical lines in Fig. 2 and Table 1 This discrepancy is acceptable for global models because it has been suggested that the error due to different spatial sampling of global models (∼ 200 km) and point observations was up to 160 % (Schutgens et al, 2016). In addition, BC air at the surface and in the free troposphere is sensitive to the above three processes in the Arctic, particularly during winter and spring (see Sect.…”
Section: Bc Concentration In Snowmentioning
confidence: 98%
“…The arithmetic mean of observations is 17.4 ng g −1 , larger than the geometric mean of 12.7 ng g −1 and the median of 11.8 ng g −1 (see the vertical lines in Fig. 2 and Table 1 This discrepancy is acceptable for global models because it has been suggested that the error due to different spatial sampling of global models (∼ 200 km) and point observations was up to 160 % (Schutgens et al, 2016). In addition, BC air at the surface and in the free troposphere is sensitive to the above three processes in the Arctic, particularly during winter and spring (see Sect.…”
Section: Bc Concentration In Snowmentioning
confidence: 98%
“…It is noteworthy that the actual number of degrees of freedom may be somewhat smaller, however, due to high spatial autocorrelation between sampled aerosol in each region as identified in many studies (e.g. Anderson et al, 2003;Schutgens et al, 2016;Kovacs, 2006;Santese et al, 2007;Shinozuka and Redemann, 2011). Nevertheless, the strength of the aerosol indirect forcing estimate Table 2.…”
Section: Aerosol-cloud Radiative Forcing Estimatesmentioning
confidence: 99%
“…Such timescales are not small compared with the BC atmospheric lifetime of 3-5 d, especially considering that dilution effects may lengthen the aging timescale in the real atmosphere compared with the static chamber measurements performed by Peng et al It is unclear how representative these measurements are for global and annual averages, but we know that generalizations can introduce serious errors due to spatial and temporal sampling issues (9). This implies that a simple scaling of the BC RF by the absorption enhancement factor measured by Peng et al-as performed by the authors in their table S1 and figure 4, and extended in the commentary (10)-is overly simplistic.…”
mentioning
confidence: 99%